(untitled) (African Journal of Biomedical Research, 2020)
Mutations in the 3’UTR and D543N regions of the solute carrier 11a1 protein (SLC11A1) gene have been found to strongly increase the risk of several diseases caused by intracellular organisms such as M. tuberculosis. The aim of this study was to screen for polymorphisms in the 3’UTR and D543N regions of SLC11A1 gene with the goal of understanding the genetic dynamics of tuberculosis and schistosomiasis co-infection in a Nigerian adult population. A cross-sectional study was carried out with 185 participants who were screened for intestinal and urinary helminthiases using microscopic examination of stool and urine respectively; latent tuberculosis using skin tuberculin test; and active tuberculosis using sputum microscopy. PCR-RFLP analyses were carried out on extracted DNA for detection of SLC11A1 gene polymorphisms. Participants filled questionnaires from which information on awareness, clinical and family histories and lifestyles were obtained. There were no polymorphisms observed. 32% had urinary schistosomiasis and 0.1% had intestinal helminthiasis suggesting that both types of infections could occur independently in the same population. The prevalence of coinfection with schistosomiasis and tuberculosis was 6.5%. This observation suggests an immunomodulation during schistosomiasis and latent tuberculosis co-infection. The absence of polymorphisms did not support the hypothesis that co-infection with schistosomiasis and latent tuberculosis might play a role as a risk factor during the development of active tuberculosis.